Impact Of Security And Interface Design On Customer Adoption Of Internet Banking: A Comparative Study Of Malaysia And Singapore - Dauda, Yahya (2006)
The study examines the perceived e-commerce security influence on adoption of Internet banking, determine the role of interface design (front-end) on consumer adoption, idebtified national environmental factors such as attitude, subjective norms, and perceived behavioral control factors towards adoption, and compare these factors with Singapore Internet banking adoption.